Examining Financial and Macroeconomic Drivers of NPF in Islamic Rural Banks of Indonesia - Alfaina Zia Inayati; Ruspita Rani Pertiwi (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
Islamic Rural Banks (BPRS) play an important role in promoting financial inclusion in Indonesia, particularly for micro and small enterprises. However, the high Non Performing Financing ratio indicates the poor quality of financing and risk management, which disrupts intermediation functions and threatens the stability of banks. This study aims to analyze the influence of financial and macroeconomic variables on BPRS NPF in the short and long term, using the Vector Error Correction Model approach based on monthly data from January 2021 to December 2024. The analysis results indicate that in the short term, the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and inflation significantly increase NPF, whereas Gross Domestic Product (GDP) does not have a significant effect. In the long term, CAR and inflation continue to have a positive impact, while FDR and GDP are not significant. These findings highlight the need for BPRS to strengthen risk management systems, improve financing selection processes, and adjust BPRS operational strategies to macroeconomic dynamics. OJK needs to encourage the implementation of early warning systems and prudent financing limits, while the government needs to maintain macroeconomic stability, particularly in controlling inflation, to support the resilience and sustainability of BPRS in the future.